Review on Resistive Termination Techniques Driven by Wireline Channel Behaviors - Changjae Moon; Minsoo Choi; Myungguk Lee; Byungsub Kim (IEEE Open Journal of the Solid-State Circuits Society)
From the perspective of channel behaviors, we review several design techniques of resistive termination for wireline applications. Termination impedances strongly affect the channel behaviors. Their impacts vary a lot depending on the types of interconnects and the circuits. Therefore, termination impedances must be appropriately designed for the target applications. In this article, first, we explain an intuitive analytical transfer function model of wireline channels. The model allows designers to easily and intuitively understand the impacts of the termination resistances on the channel behaviors. Second, we review various resistive termination techniques for LC-dominant channels and discuss their design tradeoffs. Especially, we theoretically explain the relaxed impedance matching technique, which allows designers to violate impedance matching for design improvements at the cost of a negligible penalty in signal integrity. Third, we review various resistive termination techniques for RC-dominant channels and their design tradeoffs. We especially emphasize and theoretically explain why and how the design tradeoffs by resistive terminations in RC-dominant channels are different from the ones in LC-dominant channels.